Potentiometric quantification and speciation of oxygenated groups in humic substances using BEST7 software - Vaz, Denise de Oliveira; Neves Fernandes, Andreia; Szpoganicz, Bruno; Sierra, Maria Marta de Souza (Eclética Química, 2010)
In this study the BEST7 software was employed to quantify different classes of functional groups and to model the proton titration behavior of humic substances. To illustrate the process, the Suwannee River fulvic acid of the IHSS (International Humic Substances Society) was used. Five categories – two classes of phenolic groups (phenol and cathecol), two classes of carboxylic groups (benzoic and phtalic) and the combination between them (salicylic) - of oxygenated groups were considered as being responsible for the potentiometric behavior of the sample and were quantitatively determined. The most and the least abundant groups were cathecol (3.300 0.010 mmol g-1) and phenol (1.225 0.070 mmol g-1), respectively. The estimated equilibrium constants were also determined and were in good agreement with the literature values for phenol and cathecol groups and for benzoic, phtalic and salicylic acids. Distribution diagrams of the species were generated with the software SPE and SPEPLOT.